Integration of Mathematical and English Skills in Learning in the Era of Society 5.0: Challenges and Opportunities for Generation Alpha - Hardika Saputra; Yayuk Primawati; Anita Puspa Meilina (International Journal of Mathematics and Science Education, 2025)
This study explores the integration of mathematical and English language skills in the education of Generation Alpha, particularly in the context of Society 5.0. Using a Systematic Literature Review (SLR), the research analyzes existing literature to examine the role of these skills in shaping the future educational landscape. The findings suggest that both mathematical and English language skills are crucial for preparing students for the challenges of a technology-driven society. However, challenges such as gaps in educational resources and the digital divide persist. Opportunities arise from leveraging technology to enhance both subjects simultaneously, and project-based learning methods have shown promise. Furthermore, these skills are increasingly vital in the context of Society 5.0, where digital transformation, artificial intelligence, and technological advancement are central. This paper concludes by emphasizing the importance of integrating mathematical and English language skills to ensure that Generation Alpha is adequately prepared for future societal needs.